Prevalence and predictors of co-occurring functional seizure in patients with epilepsy at a tertiary care center in Makkah - Amal Mohammed Alkhotani; Hanadi Abualela (Annals of Saudi Medicine)
BACKGROUND: A functional seizure (FS) is a paroxysmal event that resembles epileptic seizures (ES) but without associated changes in cortical activity. OBJECTIVE: To assess the prevalence of FS among ES patients admitted to the epilepsy monitoring unit (EMU) in King Abdullah Medical City (KAMC). DESIGN: A retrospective cohort study. SETTING: EMU at KAMC PATIENTS AND METHODS: EMU database from 2015 to 2023 were reviewed. Patients were included in the study if they had a diagnosis of epilepsy and recorded seizure during admission. MAIN OUTCOME MEASURES: The prevalence and the predictors of FS developments among patients with ES. SAMPLE SIZE: 198 patients. RESULTS: The prevalence of FS was 10.6%. Significant risk factors associated with FS were income (18.6% vs 8.4% P=.048), focal epilepsy (66.7% vs 33.3% for generalized P=.004), frontal localization (38.5 versus 14.3% of temporal localization P=.041), on 5 antiseizure medications (ASMs) (75% versus 3% of on one ASM P=.001), receiving phenytoin (PHY) (46.2% vs other ASMs, P=.001), on psychiatric medications before EMU (29.4% vs. 8.8%) and those on the same medication after the EMU (35.6 % vs. 3.3%) (P=.008 and .001, respectively). Around 33.3% of FS cases had a major depressive disorder (MDD), 19% had a generalized anxiety disorder (GAD) and 14.3% were diagnosed with both MDD and GAD compared to without FS 4%, 2.3%, and 4.5%, respectively (P=.001). Multiple stepwise logistic regression analysis identified additional risk factors including male gender (odds ratio [OR] 3.0, 95% CI: 2.4–47.3; P=.048), shorter epilepsy duration (OR 0.8, 95% CI: 0.6–1.0; P=.046), history of head trauma (OR 5.5, 95% CI: 1.4–25.7; P=.047) and intellectual disability (OR 17.5, 95% CI: 1.4–39.2; P=.044). CONCLUSION: Patients with combined disorders are more likely to be male, shorter epilepsy duration, had salary income, focal epilepsy, frontal localization, history of head trauma, intellectual disability and be on higher ASMs, phenytoin as ASMs, depression, anxiety and more likely to be on psychiatric treatment. LIMITATIONS: The study was a retrospective study.